The prion-like properties of amyloid-beta peptide and tau: Is there any risk of transmitting alzheimer's disease during neurosurgical interventions? (2020)
Recent studies have recognized similarities between the peptides involved in the neuropathology of Alzheimer’s disease and prions. The Tau protein and the Amyloid β peptide represent the theoretical pillars of Alzheimer’s disease development. It is probable that there is a shared mechanism for the transmission of these substances and the prion diseases development; this presumption is based on the presentation of several cases of individuals without risk factors who developed dementia decades after a neurosurgical procedure. This article aims to present the role of Aβ and Tau, which underlie the pathophysiologic mechanisms involved in the AD and their similarities with the prion diseases infective mechanisms by means of the presentation of the available evidence at molecular (in-vitro), animal, and human levels that support the controversy on whether these diseases might be transmitted in neurosurgical interventions, which may constitute a wide public health issue.